PENGEMBANGAN LKPD BERBASIS MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA MTS SWASTA MUHAMMADIYAH 29 STABAT - Akbar, Ilham; Irwan, Irwan (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
This research aims to find Learner Worksheets (LKPD) using the Discovery Learning learning model on flat-sided space building material for students of MTs Swasta Muhammadiyah 29 Stabat class VIII-1. The quality of the developed product is assessed based on the aspects of validity, and practicality. The mathematics learning development procedure refers to the 4-D development model, namely Define, Design, Develop, and Disseminate. Due to the researcher's limitation, the research was conducted up to the develop stage. The subjects of this study were students of class VIII-1 MTs Swasta Muhammadiyah 29 Stabat. The instrument used to measure the quality of mathematics learning developed is the LKPD assessment sheet. The findings of the research conducted are the assessment of the quality of the validity of mathematics learning using LKPD based on the Discovery Learning learning model meets the valid criteria based on the average score of LKPD which is 82% with very valid criteria. The quality of the practicality of learning mathematics meets the practical criteria based on the average score of the student response questionnaire 78% of the maximum 100% with very practical criteria. Keywords. Development of Learner Worksheets, Discovery Learning Model